The effects of urbanisation on bee and wasp communities in Cape Town, South Africa - Walker, Gemma (Department of Biological Sciences, 2023)
Bees and wasps provide essential regulatory ecosystem services by pollinating urban plants. However, there are massive global declines in many insect groups, and little is known about the impacts of urbanisation on pollinators in rapidly developing areas of Africa. South Africa is one of the most urbanised and biodiverse countries in Africa, and the Cape Floristic Region, one of the country's most important centres of biodiversity, is the only area in the world where bee and plant diversity hotspots coincide. Within the centre of this hotspot (Durbanville, Cape Town), I investigated the effects of urbanisation and availability of floral resources on bee and wasp (pollinator) diversity, community composition, and nesting guild distribution across an urbanrural/natural gradient. Using pan traps, specimens were collected from 18 sites in the austral spring of 2019 and 2020. A total of 433 bee and 45 wasp specimens, comprising of 45 bee and 27 wasp morphospecies respectively, were collected. Bees from the family Halictidae (particularly Seladonia and Patellapis species) were the most abundant. Except for Apis mellifera, all other bee species were solitary, and most (86.7%) collected pollen from flowers. A total of four different nesting guilds were identified, with the most common being ground-nesters (68.9%). Floral resources, rather than the degree of urbanisation, had a strong positive effect on pollinator diversity and community composition. The same trend was observed for nesting guilds at both the community and individual guild level. This study supports the development of several costeffective and achievable conservation initiatives, such as adopting no-mow periods during austral spring and developing small-scale bee-friendly floral-rich patches, which can be undertaken by existing municipal structures and private landowners alike. Urban spaces in Cape Town have the potential to support important pollinator diversity, but more research is needed. Suggested future studies include investigating the ways pollinator diversity and community composition is influenced by 1) individual floral species and characteristics, 2) the size, shape, and location of habitat/floral patches, and 3) the effects of urban warming.